Answer:
1. 47 correct, 0 wrong and 3 unanswered
2. 48 correct, 1 wrong and 1 unanswered
Step-by-step explanation:
Given;
Total number of questions = 50
For correct answers = 2
For wrong answers = -2
Unanswered questions = 0
Yash scored 94 marks
Let c, w and u represent the number of correct, wrong and unanswered questions
2×c - 2 × w + 0×u = 94
2c -2w = 94 .....1
And;
c + w + u = 50 .....2
We have 2 equations and 3 unknowns
By observing the problem, we can see two possible solutions;
Case 1: Assuming he did not miss (get wrong) any answer;
He needs to score 47 answers right;
47 × 2 = 94
Then;
c = 47 w = 0 and u = 50 - (47+0) = 3
47 correct, 0 wrong and 3 unanswered
Case 2: Assuming he got one answer wrong;
He would need to score one more answer right compared to the first case;
(47+1) × 2 - 1 × 2 = 96 - 2 = 94
c = 47+1 = 48
w = 1
u = 50 - (48+1) = 1
So he need to score 48 correct answers, 1 wrong answer and 1 unanswered.
Lliana started to evaluate the function f(x)=2x^2-3x+7 for the input value 2. What is the value of the function when x=2?
Answer:it is 9 because you subtract 6 from the 8 and then you add 2 and 7 to get 9
Step-by-step explanation:
Which is a simplified form of the expression 2(2j + 3) – 3j? A. -j + 3 B. 2j + 3 C. j + 6 D. -j + 6
Answer:
C. j + 6
Step-by-step explanation:
2(2j + 3) - 3j
multiply each term in the parentheses by 2
2 x 2j + 2 x 3
calculate the product
4j + 6 -3j
collect like terms by subtracting their coefficients
(4 - 3)j
then subtract the numbers
1j
when the term has a coefficient of 1, it doesn't have to be written
j
then plug in the other number and that's your answer
j + 6
Answer:
The answer is C).Step-by-step explanation:
C. j + 6
Hope this helps!! :)
Please answer correctly !!!!!!!! Will mark brainliest !!!!!!!!!!
Answer:
x^2+6x+9
Step-by-step explanation:
x^2 +6x
Take the coefficient of x
6
Divide by 2
6/2 = 3
Square it
3^2 = 9
Add 9 to each side
x^2+6x+9
PLZZZ HELPP 3+7 - 1/2 is an example of A. a numerical equation B. an algebraic equation C. a numerical expression D. an algebraic expression
Answer:
A. a numerical equation
Step-by-step explanation:
2/5 y + 1/5 x -0.2y - 6 + (-2)
Answer:
[tex]0.2y+0.2x-8[/tex]
Step-by-step explanation:
[tex]\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)[/tex]
[tex]=\frac{2}{5}y+\frac{1}{5}x-0.2y-6-2[/tex]
[tex]=\frac{2}{5}y-0.2y+\frac{1}{5}x-6-2[/tex]
[tex]\frac{2}{5}y-0.2y[/tex]
[tex]=y\left(\frac{2}{5}-0.2\right)[/tex]
[tex]\frac{2}{5}-0.2=0.2[/tex]
[tex]=0.2y[/tex]
[tex]=0.2y+\frac{1}{5}x-6-2[/tex]
[tex]\frac{1}{5}x[/tex]
[tex]=\frac{1\cdot \:x}{5}[/tex]
[tex]=\frac{x}{5}[/tex]
[tex]=0.2y+\frac{x}{5}-6-2[/tex]
[tex]=0.2y+0.2x-8[/tex]
The dimensions of a box are x, 2x, and 3x. Each dimension is increased by 3. Calculate the volume of the box.
Answer:
The volume of the box would be 6x³+33x²+54x+27.
Step-by-step explanation:
The new dimensions of the box would be (x+3), (2x+3), and (3x+3). Since the volume of a rectangular prism are calculated by multiplying the length, width, and depth, we can just multiply all three of these dimensions together to come up with the answer.
Using foil on the first two terms originally you get (x+3)×(2x+3)= 2x²+3x+6x+9 which can be simplified to 2x²+9x+9.
Then you multiply this equation by (3x+3). (2x²+9x+9)×(3x+3)= 6x³+6x²+27x²+27x+27x+27 which can be simplified to 6x³+33x²+54x+27.
Answer:
6x³+33x²+54x+27
Step-by-step explanation:
dimensions are now:
x+3, 2x+3, 3x+3
Volume
V=lwhV= (x+3)(2x+3)(3x+3)= 3(x+1)(x+3)(2x+3)= 3( x² + 4x+3)(2x+3)= 3(2x³+11x²+18x+9)=6x³+33x²+54x+27Find the value of n 5^10 ÷ 5^8=(1/5)^n
Answer:
5^10 / 5^8 = 5^2 = 25 so the equation becomes 25 = (1/5) ^ n. This means that n = -2.
Answer:
[tex]n=-2[/tex]
Step-by-step explanation:
[tex]\frac{5^{10}}{5^8}=(\frac{1}{5})^n[/tex]
Use the law of exponents.
[tex]5^{10-8}=\left(\frac{1}{5}\right)^n[/tex]
1/5 can be written with a base of 5.
[tex]5^{10-8}=\left(5^{-1}\right)^n[/tex]
Cancel the base 5 on both sides.
[tex]10-8=-1\times \:n[/tex]
[tex]2=-n[/tex]
Multiply both sides with -1.
[tex]n=-2[/tex]
Which of the following choices evaluates -2x2 + 4x, when x = -2?
Answer:
x = -2
-2(-2^2) + 4(-2)
-2(4) + -8
-8 + -8Answer = -16 is the answer.Please answer correctly !!!!!! Will mark brianliest !!!!!!!!!!!
Answer: 2
Step-by-step explanation:
determine the kinetic energy of 745-kg roller coaster car that is moving with a speed of 14.9 m/s
Answer:
≈82698.73 kg m²/s
Step-by-step explanation:
K.E.=1/2mv²=1/2×745×14.9²=82698.725 kg m²/s
Please answer correctly !!!!!!! Will mark brainliest !!!!!!!!!!!
Answer:
et's solve your equation step-by-step.
(x+3)2−1=35
Step 1: Simplify both sides of the equation.
x2+6x+8=35
Step 2: Subtract 35 from both sides.
x2+6x+8−35=35−35
x2+6x−27=0
Step 3: Factor left side of equation.
(x−3)(x+9)=0
Step 4: Set factors equal to 0.
x−3=0 or x+9=0
x=3 or x=−9
Answer:
x=3 or x=−9
Answer:
Add 1 to each side
Take the square root of each side
Subtract 3 from each side
Step-by-step explanation:
(x+3)^2 -1 = 35
Add 1 to each side
(x+3)^2 -1+1 = 35+1
(x+3)^2 = 36
Take the square root of each side
sqrt ((x+3)^2) =±sqrt (36)
x+3 = ±6
Subtract 3 from each side
x+3-3 = -3±6
x = -3±6
x = -3+6 x = -3-6
x = 3 x = -9
Emma needs 40 pieces of string to wrap presents. Each piece of string is 7.5 inches. If the ribbon is only available in feet, how many feet of ribbon does Emma need?
Answer:
2635*'fhhdgjvsvaksgwksygwi at gwjsksgeieh egg ejei
Please answer correctly !!!!!!!! Will mark brainliest !!!!!!!!!!!!!
Answer:
The discriminant is 0
That means there is one real zero
Step-by-step explanation:
3x^2 + 24x + 48
This in the form
ax^2 +bx+c
a=3 b=24 c = 48
The discriminant is
b^2 - 4ac
24^2 - 4(3)(48)
576-576
0
The discriminant is zero
That means there is one real zero
A circular rug has a radius of 10 feet. What is the area of the rug? Use 3.14 for π.
Enter your answer
Answer:
A=314 feet
Step-by-step explanation:
[tex]A=\pi r^{2}[/tex]
[tex]A=3.14*10^{2}[/tex]
[tex]A=3.14*100[/tex]
[tex]A=314 feet[/tex]
Which of these choices are quadratic equations? Check all that apply.
A. 2x – 1 = 0
B. 2x2 - 1 = 0
C. 2x2 - 1
D. 3x2 + 5x - 1 = 0
E. x - x² +5=0
F. - 4x2 + x = 0
Answer:
Quadratic Equations ⇒ D, E, F
Step-by-step explanation:
Let us say that each of these equations can only be defined as a quadratic equation if it can be factored / solved through completing the square / application of quadratic formula as solve for the value of x;
[tex]A. 2x - 1 = 0, Add + 1 to either side,\\2x = 1, Divide sides by 2,\\x = 1 / 2 ; Not Quadratic Equation[/tex]
[tex]B. 2x^2 - 1 = 0, Add + 1 to either side,\\2x^2 = 1, Divide sides by 2,\\x^2 = 2, Take | | of x, \sqrt{x} - either side \\\| x | = \sqrt{1 / 2},\\x = \sqrt{1 / 2} = - \sqrt{1 / 2} ; NotQuadraticEquation[/tex]
[tex]C. 2x^2 - 1, NotInForm - ax^2 + bx + x = 0 ; NotQuadraticEquation[/tex]
[tex]D. 3x^2 + 5x - 1 = 0, Add 1 to either side,\\3x^2 + 5x = 1, Divide sides by 3,\\x^2 + 5x / 3 = 1 / 3, Solve for a,\\2ax = 5 / 3x, Divide sides by 2x,\\a = 5 / 6, Add a^2 - ( 5 / 6 )^2 to either side,\\x^2 + ( 5x / 3 )^2 + ( 5 / 6 )^2 = 1 / 3 + ( 5 / 6 )^2, simplify,\\( x + 5 / 6 )^2 = 37 / 36, solve for x,\\x = ( \sqrt{37} - 5 ) / 6 = ( - \sqrt{37} - 5 ) / 6 ; QuadraticEquation[/tex]
[tex]E. x - x^2 + 5 = 0, Similar Form ; QuadraticEquation\\[/tex]
[tex]F. - 4x^2 + x = 0, Factor the Expression,\\- x * ( 4x - 1 ) = 0, Apply Zero Product Property,\\x = 0, and, 4x - 1 = 0,\\x = 0 = 1 / 4 ; QuadraticEquation[/tex]
The quadratic equations are:
2x² - 1 = 0
2x² - 1
3x² + 5x - 1 = 0
x - x² +5 = 0
-4x² + x = 0
Options B, C, D, E and F are the correct answer.
What is a polynomial?Polynomial is an equation written as the sum of terms of the form kx^n.
where k and n are positive integers.
We have,
A polynomial with degree 2 is called a quadratic equation.
A.
2x – 1 = 0
This is not a degree 2 equation.
B.
2x² - 1 = 0
This has degree 2.
C.
2x² - 1
This has degree 2.
D.
3x² + 5x - 1 = 0
This has degree 2.
E.
x - x² +5 = 0
-x² + x + 5 = 0
This has degree 2.
F.
- 4x² + x = 0
This has degree 2.
Thus,
B, C, D, E, and F are quadratic equations.
Learn more about polynomials here:
https://brainly.com/question/2284746
#SPJ2
For which x is f(x)?=-3
Answer:
[tex]-7[/tex]
Step-by-step explanation:
[tex]f(-3)=-7[/tex]
Find the value of x in the triangle shown below
Answer:
28°
Step-by-step explanation:
every Triangle equals to 180°
85+67=152
180-152=28
Verticle angles must have ?
Answer: Verticals angles are when 2 line intersect at a point forms 2 pairs of angles. The pairs will be opposite of each other.
The picture I have attached should give a good representation of what I mean.
The A angles are the same and the B angles are the same in the picture.
Emma spent $21.23 on two thousand bagels and a gallon of iced tea the price of the gallon of iced tea with $5.25 the following equation can be used to find d the price of the each dozen of bagels
Answer:
$21.23 - $5.25 = d
Step-by-step explanation:
if p(x) = x^99 + 99 , then find p(1)
Answer:
p(1)=100
Step-by-step explanation:
p(1) just means "substitute the value (1) in for (x) in the equation"
So,
[tex]1^{99}[/tex]+99= 100
(1 to any power is always equal to 1, including 0)
A pentagon train is made by attaching regular pentagons with 1" sides so that each pentagon, except the two on the ends, is attached to exactly two other pentagons along sides, as shown. How many inches are in the perimeter of a pentagon train made from 85 pentagons?
Answer:
There are 341 inches from the perimeter of a pentagon train made from 85 pentagons
Step-by-step explanation:
A pentagon is a polygon with five sides. A regular pentagon have all the five sides equal in length and also all the five interior angles equal.
The perimeter of a pentagon = 5l
Nof for a pentagon train attached to 1 pentagon by its sides;
The perimeter = (5 × 1 - (1-1))
Perimeter = 5
For pentagon train attached to two pentagon
Perimeter = ( 5×2 - (2-1))
Perimeter = (10 1)
Perimeter = 9
For pentagon train with n pentagon
Perimeter = ( 5× n -(n-1))
Perimeter = 5n - n+1
Perimeter = 4n + 1
∴ For pentagon train attached to 85 pentagon; where n=85
Perimeter = 4 n + 1
Perimeter = (4 × 85)+1
Perimeter = 340+1
Perimeter = 341 inches
There are 341 inches from the perimeter of a pentagon train made from 85 pentagons
????????????????????
Answer:
A) DEBBIE: 1p+4t=29
B) JOEY: 5p+2t=28
Step-by-step explanation:
What is the solutions for x in the equation -2x+14+10x=34
Answer:
x=2.5
Step-by-step explanation:
Put the like terms together, like so:
10x-2x=34-14
The result is this:
8x=20
Simplify to get:
x=2.5
Answer:
x= 2 1/2 or x=2.5
Which expression can be used to find 38 percent of 22?
Answer:
[tex]0.38 \times 22[/tex]
Step-by-step explanation:
The correct expression used to find 38 percent of 22 is
[tex]0.38 \times 22[/tex]
Which of the following describes the translation of the graph of y=x? to obtain the graph of y=-x2+3?
reflect over the x-axis and shift right 3
o reflect over the x-axts and shift up 3
reflect over the y-axis and shift down 3
Answer:
Reflect over the x-axis and shift up 3.
Answer:
Reflect over the x-axis and shift up 3
Step-by-step explanation:
Question 1 (1 point)
What is the solution set to the equation x+1=2
Question 2 (1 point)
Consider the equation x +1 = 2.
Rewrite the equation by multiplying both sides by x +1
DO NOT USE A MULTIPLICATION SYMBOL
Question 3 (1 point)
Solve the equation for
5(2x - 4) - 11 = 4 + 3x
please answer all if possible. Thanks
Answer:
See below
Step-by-step explanation:
1) x=2-1
x=1
2) (x+1)(x+1)=2(x+1)
3) 10x-20 -11 = 4+3x
10x-3x=20+11+4
7x=35
x=5
What is the slope of the line that passes through the points (-8, -3) and
(-12, -3)? Write your answer in simplest form.
Answer:
slope = 0
Step-by-step explanation:
Calculate the slope m using the slope formula
m = [tex]\frac{y_{2}-y_{1} }{x_{2}-x_{1} }[/tex]
with (x₁, y₁ ) = (- 8, - 3) and (x₂, y₂ ) = (- 12, - 3)
m = [tex]\frac{-3+3}{-12+8}[/tex] = [tex]\frac{0}{-4}[/tex] = 0
Slope is rise per run. Rise is difference of y ordinates and run is difference of corresponding x abscissa.
The slope of the line that passes through the given points is 0
Given that:The two specified points are: (-8,-3), and (-12, -3)To find:
Slope of the line that passes through given points.
In graphing, we use Cartesian plane and assume y axis to be perpendicular and mostly we take height or depth related stuffs on y axis, that's why y ordinates will be considered to calculate the rise and x axis is like flat ground, thus x abscissa will be used to calculate the run.
Let the points' coordinates are denoted by symbols as:
[tex](x_1, y_1) = (-8,-3)\\ (x_2, y_2) = (-12, -3)\\ [/tex]
[tex]slope = \dfrac{rise}{run} = \dfrac{y_2 - y_1}{x_2 - x_1} = \dfrac{(-3) - (-3)}{(-12)-(-8)} = \dfrac{0}{-4} = 0[/tex]
Slope is zero means you run whatever, the rise is 0, which means the line is not going to rise and stay flat (horizontal).
Learn more about slope of straight lines here:
https://brainly.com/question/1892775
Evaluate the expression for p = 4.
p^2=
4^2 = 4 * 4.
4 * 4 = 16.
Therefore, p ^2 = 16.
Answer:
16
Step-by-step explanation:
i showed the work in the picture above
plslslslsl help ASAP you win win brainlist
Answer:
78 dollars
Step-by-step explanation:
Take the prices and multiply by the percent commission
778 * 10 %
Change to decimal form
778 * .10
77.80
Round to the nearest dollar
78
Answer:77.80
Step-by-step explanation:
what does 9n-2<7+20 equal?
Answer:
[tex]n<\frac{29}{9}\\n<3.222222.....\\[/tex]
n ≈ 3
Step-by-step explanation:
9n-2<7+20
[tex]9n-2<27 \leftarrow \text {Combine Like Terms}\\9n-2+2<27+2 \leftarrow \text {Addition Property of Equality}\\9n<29\\\frac{9n<29}{9} \leftarrow \text {Divsion Property of Equality}\\\boxed{n<\frac{29}{9}}[/tex]